A methods engineering study of Mars Incorporated - Arsenal, Ray Angelo A. (College of Engineering, 1996)
MARS Incorporated is a small scale company in Bo. Canumay, Valenzuela, engaged in the weaving of plain fabric, or greige cloth, from warp beams and weft spools. It has been in business since 1988. Currently, operations are done in two buildings : a larger one housing the looms, and a smaller one where other operations are done. There are four management people and twenty-seven line workers. The present production system consists of four major steps, namely reaching-in, weaving, inspection and folding, in that order. Initial observations pointed toward reaching-in as the source of the bottlenecks. However, in the course of the study it was noted that the real cause of the snags was to be found in the inspection operation, which at times would have a pending backlog, despite the weaving section not being a full capacity. Other secondary problems were noted, particularly in the noise and lighting aspects of the working environment. Also, the systems and procedures of the company were studied, with emphasis on the forms and flow of forms. With those problems in mind, alternavies were sought and evaluated on the basis of cost, benefit to workers, benefit to management, and environmental impact. The areas of concern were narrowed to the plant layout, the work sequence, the working environment, and the systems and procedures. Among others, examples of alternatives were the making of new openings to streamline the flow of materials, the purchase of fixtures, and the do nothing option. After ranking the alternatives, the most feasible solutions were to hire another cloth inspector and a contractual janitor, emphasize and enforce safety procedures, have shelves made for spools, and purchase better chairs for the reach-in stations, to name a few.